Oltmans Receives 2013 Yoram J. Kaufman Unselfish Cooperation in Research Award - Thompson, Anne M. (AGU, 2014)
Samuel “Sam” Oltmans, an AGU Fellow since 2007, was head of the National Oceanic and Atmospheric Administration's (NOAA) Global Monitoring Division Ozone and Water Vapor group for more than 30 years. He is currently a senior research scientist at the Cooperative Institute for Research in the Environmental Sciences (CIRES) of the University of Colorado at Boulder.